Temporary Clamping of Bilateral Common Iliac Artery During Cesarean Hysterectomy for the Management of Placenta Percreta. (July 2020) - Sucu, Seyhun; Ozcan, Huseyin Çaglayan; Misirlioglu, Mesut; Guralp, Onur; Kaya, Baris
Abstract: Objective: To evaluate whether bilateral common iliac artery (CIA) temporary clamping reduces blood loss during cesarean-hysterectomy of placenta percreta cases. Study design: A total of 32 women, who underwent cesarean-hysterectomy under bilateral CIA temporary clamping (n = 12) and without any arterial clamping or ligation ( control group, n = 20 ) due to placenta percreta in Gaziantep University Hospital were retrospectively evaluated. The intra- and postoperative outcomes such as blood loss, blood transfusion and complications were compared between the two groups. Results: Age, parity, body-mass-index and gestational-age were similar in the two groups. The estimated blood loss was lower in the temporary clamping of CIA group than the control group (595 ± 172 mL vs 1450 ± 662 mL, P < 0.001) . The number of intraoperative packed-red-blood-cells (0.17 ± 0.58 units vs 1.85 ± 1.46 units, P = 0.002) and fresh-frozen-plasma (0.17 ± 0.58 units vs 1.7 ± 1.49 units, P = 0.005) transfusions were lower in the CIA temporary clamping group than the control group. The rate of women, who received blood/blood products were significantly lower in the CIA temporary clamping group compared to the control group ( 75 % vs 16 %, P = 0.001). Duration of operation was longer in the CIA temporary clamping group (140 ± 38 min vs 90 ± 25 min, p = 0.001) . No complication or maternal death was encountered during this study. Conclusion: Bilateral CIA temporary clamping method reduces the intraoperative blood loss and the amount of intraoperative blood/blood product transfusions during cesarean-hysterectomy due to placenta percreta.